PENGGUNAAN METHYL EUGENOL TERHADAP SERANGAN LALAT BUAH (Bactrocera sp.) PADA TANAMAN CABAI KERITING (Capsicum annum L.) DI KOTA TOMOHON - Karni Frastika Dondo; Jimmy Rimbing; Caroulus Rante (COCOS, 2018)
ABSTRACT Â Curly chili (Capsicum annum L.) is one of the many horticultural commodities needed in daily life so that its needs continue to increase along with population growth and technological progress. One of the main pest species that attacks fruits and vegetables in Indonesia is Bactrocera sp. Methyl eugenol is reported sp to be able to control fruit flies in mango, guava, starfruit, melon, jackfruit, guava, tomato, red pepper and bitter melon. The aim of this study was to determine the level of fruit damage by Bactrocera sp. Fruit flies. in the use of methyl eugenol in curly chili plants in Tomohon City, especially in the villages of Kinilow, Kakaskasen, and Matani. The duration of the study lasted for three (months), namely from February to April 2018. This research was carried out by survey method or by direct observation at the research location. Results of research on percentage of Bactrocera sp. in the land of methyl eugenol from the first and second weeks of 21.53% and 20.78%, while in the third week, the percentage of attacks was 18.86% followed by the observation of the fourth and fifth weeks increased by 24.34% and 33.86%. While the land of farmers experienced a decrease in the percentage of attacks from the first week, the second was 16.19% and 15.78%, then followed in the third, fourth and fifth weeks, the percentage of attacks increased by 17.47%, 18.54% and 18.7% . Whereas on land that is left to attack Bactrocera sp. from the first week of 16.09%, the second week was 21.9%, and in the third and fourth weeks the attack rate increased by 25.38% and 26.52%, followed by the fifth week of the attack level which increased to 30.56%. Â Keywords: Percentage, Bactrocera sp. Curly chili